Adipose Extracellular Vesicles in Intercellular and Inter-Organ Crosstalk in Metabolic Health and Diseases - Huang, Zhe; Xu, Aimin (Frontiers in Immunology, 2021)
Adipose tissue (AT) is a highly heterogeneous and dynamic organ that plays important roles in regulating energy metabolism and insulin sensitivity. In addition to its classical roles in nutrient sensing and energy storage/dissipation, AT secretes a large number of bioactive molecules (termed adipokines) participating in immune responses and metabolic regulation through their paracrine and/or endocrine actions. Adipose-derived extracellular vesicles (ADEVs), including exosomes, microvesicles (MVs), and apoptotic bodies, have recently emerged as a novel class of signal messengers, mediating intercellular communications and inter-organ crosstalk. In AT, ADEVs derived from adipocytes, immune cells, mesenchymal stem cells, endothelial cells are actively involved in modulation of immune microenvironment, adipogenesis, browing of white adipose tissue, adipokine release and tissue remodeling. Furthermore, ADEVs exert their metabolic actions in distal organs (such as liver, skeletal muscle, pancreas and brain) by sending genetic information (mainly in the form of microRNAs) to their target cells for regulation of gene expression. Here, we provide an updated summary on the nature and composition of ADEVs, and their pathophysiological functions in regulating immune responses, whole-body insulin sensitivity and metabolism. Furthermore, we highlight the latest clinical evidence supporting aberrant production and/or function of ADEVs as a contributor to obesity-related chronic inflammation and metabolic complications and discuss the opportunities and challenges in developing novel therapies by targeting ADEVs.